2016
DOI: 10.5194/nhess-2016-56
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transfer Entropy between South Atlantic Anomaly and Global Sea Level for the last 300 years

Abstract: Abstract. An innovative information-theoretic tool, transfer entropy, has been applied to measure the possible information flow and sense between two real time series: the South Atlantic Anomaly (SAA) area extent at the Earth's surface and the Global Sea Level (GSL) rise anomalies for the last 300 years. This connection was previously suggested considering only the long term trend. Now we study the possibility of that this relation also happens in shorter scales. The new results seem to support again this hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
(79 reference statements)
1
2
0
Order By: Relevance
“…This result is in agreement with the argument made by Svensmark (2007). However, there are few works reporting the possible indirect influence of the geomagnetic field on climatic variations during the last century (e.g., Vieira and da Silva, 2006;Courtillot et al, 2007;Frigo et al, 2013;Campuzano et al, 2016). Frigo et al (2013) investigated the spectral coherence between the 11-and 22-year solar activity cycles and the yearly average temperatures recorded during the last century at four weather stations located in southern Brazil's coastal region.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…This result is in agreement with the argument made by Svensmark (2007). However, there are few works reporting the possible indirect influence of the geomagnetic field on climatic variations during the last century (e.g., Vieira and da Silva, 2006;Courtillot et al, 2007;Frigo et al, 2013;Campuzano et al, 2016). Frigo et al (2013) investigated the spectral coherence between the 11-and 22-year solar activity cycles and the yearly average temperatures recorded during the last century at four weather stations located in southern Brazil's coastal region.…”
Section: Introductionsupporting
confidence: 86%
“…Some of these works suggest that climatic modulation occurs indirectly, through the action of galactic cosmic rays (GCRs) (e.g., Svensmark and Friis-Christensen, 1997). GCRs are predominantly positively electrically charged particles; although these contribute very little to the energy input, they are very important in the ionization processes in the Earth's atmosphere (Carslaw et al, 2002). The entrance of GCRs to the atmosphere is modulated by the magnetic fields of the Sun and the Earth.…”
Section: Introductionmentioning
confidence: 99%
“…Their results suggested that greenhouse gases are primary contributors to the recent climate variability. The authors of [ 23 ] studied the information exchange between the South Atlantic anomaly and global sea level for the last 300 years using TE and concluded that larger information is exchanged from the south Atlantic anomaly to global sea-level rise than vice versa. However, these studies relied only on a single TE estimation technique (binning).…”
Section: Introductionmentioning
confidence: 99%